High-Sensitivity C-Reactive Protein Levels in Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD), Metabolic Alcohol-Associated Liver Disease (MetALD), and Alcoholic Liver Disease (ALD) with Metabolic Dysfunction - Seong-Uk Baek; Jin-Ha Yoon (Biomolecules)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a recently introduced term for steatotic liver disease (SLD). Although the inflammatory process is central to the pathogenesis of SLD, research investigating the differences in systemic inflammation across various SLD subtypes as well as sex differences is limited. This population-based, cross-sectional study investigated the association between SLD subtypes and high-sensitivity C-reactive protein (hs-CRP) levels among Korean adults (N = 20,141; mean age: 50.8 ± 16.7 years). The participants were classified into five groups that included no SLD, MASLD, metabolic alcohol-associated liver disease (MetALD), alcoholic liver disease with metabolic dysfunction (ALD with MD), and other SLDs. The median (Q1, Q3) value of the hs-CRP level was 0.54 mg/L (0.33, 1.04). Among men, compared to levels in the no SLD group, the MASLD, MetALD, and ALD with MD groups were associated with 41.9% (95% confidence interval [CI]: 35.1–49.1%), 46.8% (95% CI: 35.0–59.6%), and 51.8% (95% CI: 30.0–77.2%) increases in hs-CRP levels, respectively. The association between SLD subtypes and hs-CRP levels was stronger among women, and compared to the levels in the no SLD group, the MASLD, MetALD, and ALD with MD groups were associated with 81.5% (95% CI: 73.6–89.8%), 84.3% (95% CI: 58.1–114.8%), and 98.2% (95% CI: 38.0–184.8%) increases in hs-CRP levels, respectively. In conclusion, our findings indicate a varying profile of systemic inflammation across SLD subtypes, with more pronounced increases in hs-CRP levels in women with SLDs.